Properties of Objects and Their Transformation on the Plane (Indian Journal of Advanced Mathematics (IJAM), 2026)
Every function has its properties relative to the mechanisms of a circle, since cycles repeat. Such that all equations factor so well within its definition, that clearly, every circle has a radius that is greater than zero. If the radius expands by any set of numbers, then it is transforming. Hence, every object under it expands at a specific ratio. To a point that it is pretty natural for phenomena to repeat, given that it is within the area of its circumference. Although the events are not the same. Functions tend to approximate mathematical constants, primarily due to their periodicity of behaviour, as they are cyclic under certain conditions. The centre of a black hole is a point, so much like that of a circle. Since, therefore, objects alter the state of dimensions they occupy, so that relative to the point of reference, they either appear as paraboloids, ellipses, hyperbolas, or circles, depending on the context.